Synchronization of moving integrate and fire oscillators - Prignano, Luce (2012)
We present a model of integrate and ﬁre oscillators that move on a plane. The phase of the oscillators evolves linearly in time and when it reaches a threshold value they ﬁre choosing their neighbors according to a certain interaction range. Depending on the velocity of the ballistic motion and the average number of neighbors each oscillator ﬁres to, we identify diﬀerent regimes shown in a phase diagram. We characterize these regimes by means of novel parameters as the accumulated number of contacted neighbors.